The Effect Of Performance, Capital Structure, Owner Structure, Inventory Intensity And Firm Size As The Control Variable For Tax Aggressiveness In Manufacturing Company For Period 2013 â€“ 2018 Listed At Indonesia Stock Exchange - Novita, Novita (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This study discusses the effect of variable profitability, leverage, ownership structure, inventory intensity of taxes and firm size as a control variable partially. The sample used in this study is 144 manufacturing companies listed on the Indonesia Stock Exchange (IDX) using a purposive sampling technique with data panels for the period 2013-2018. The data used in this study is secondary data containing annual financial reports. The method of data analysis using multiple linear regression (OLS Multiple Regression Analysis), obtained results: all negative variables are significant to tax aggressiveness unless the leverage variable does not have a significant effect. While variable control (firm size) has no influence on tax aggressiveness and cannot be used as a variable control.Â Keywords: Profitability, Inventory Intensity, Ownership Structure, Leverage, ETRÂ REFERENCESAgusti, Wirna Yola. 2014. The Effect of Profitability, Leverage, and Corporate Governance on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange in period 2009-2012 . Journal of Accounting, Volume 3 No.2 April.Brigham, Eugene F dan Joel F Houston. 2006.Fundamentals of Financial Management. Jakarta:Salemba Empat.Cahyono, Andini dan Raharjo. 2016.The Influence of the Audit Committee, Institutional Ownership, Board of Commissioners, Company Size (Leverage), Leverage (Der) and Profitability (Roa) Against Tax Avoidance Actions. Journal of Accounting, Volume 2 No.2 March 2016.Chen, S., Chen X et.al. 2010. Are Family Firms more Tax Aggressive than Non-FamilyFirms?. Journal of Financial Economics.Dewi, A. A., &Dewi, L. G. (2014). Transparency Information moderates the effect of tax aggressiveness on the value of mining companies on the Indonesia Stock Exchange. Journal of Accounting10, 211-230.Dewinta, Ida Ayu Rosa., dan Putu Ery Setiawan. 2016. The Influence of Company Size, Company Age, Profitability, Leverage and Sales Growth on Tax Avoidance of Manufacturing Companies that are listed on the Indonesia Stock Exchange 2011-2014. Thesis: Universitas Udayana.Frank, M.M., Lynch, L.J., & Rego, S.O. (2009) â€œTax reporting aggressiveness and its relation to aggressive financial reportingâ€. The Accounting Review, 84, 467-496.Gul, Ferdinand A., Simon Yu Kit Fung and Bikki Jaggi. 2017. Earning Quality: Some Evidence on The Role of Auditor Tenure and Auditorsâ€™s Industry Expertise. Journal of AccountingHarahap, Sofyan Safri. 2008.Critical Analysis of Financial Statements. Jakarta:PT Raja Grafindo Persada.Ichsan Pamungkas. 2013Analysis of Factors Affecting Good Corporate Governance Rating. Faculty Economic Journal Universitas Diponogoro Semarang. www.ejournal.undip.ac.id (Diakses 22 Maret 2018).Jensen, M. & Meckling, W., (1976) â€œTheory of The Firm: Managerial Behaviour, Agency Cost and Ownership Structureâ€. Journal of Financial Economics, 3, 305-360.Maharani, I. G., dan Suardana, K. A. 2014. The Effect of Corporate Governance Profitability and Executive Characteristics on Tax Avoidance of Manufacturing Companies Registered on the IDX. Accounting E-Journal UniversitasUdayana, 525-539.Merslythalia, Dy Retta dan Mienati Somya Lasmana, 2016.The Effect of Executive Competence, Company Size, Independent Commissioners, and Institutional Ownership on Tax Avoidance. Scientific Journal of Accounting and Business, Vol.11, No. 2, July 2016.Novriyanti. 2016. The Effect of Company Size, Leverage, Profitability, Independent Commissioners and Audit Committees on Tax Avoidance in Goods and Consumption Industry Companies listed on the Indonesia Stock Exchange Period 2011-2014. Thesis:Universitas Marititm Raja Ali Haji.Permanasari, Wien Ika. (2010).The Influence of Management Ownership, Institutional Ownership, and Corporate Social Responsibility Towards Company Value. Semarang: Diponegoro University.Prakosa, K. B. 2014. The Effect of Profitability, Family Ownership and Corporate Governance on Tax Avoidance in Indonesia. Journal of the Indonesian Islamic University.PSAK Nomor 14 Revisi 2008 oleh IkatanAkuntan IndonesiaRistadelvina. 2017. The Effect of Corporate Governance Index, Family Ownership, and Institutional Ownership on Equity Costs and Debt Costs: Empirical Study of Manufacturing Companies Listed on the IDX. Thesis. Accounting Department, Faculty of Economics, University of Indonesia.Rusydi, M. Khoiru. 2013. The Effect of Company Size on Aggressive Tax Avoidance in Indonesia. Journal of Multiparadigm Accounting, Vol. 4 Number 2, p. 165-329 August 2013Sudana, I Made. 2011. Corporate Financial Management: Theory and Practice. Surabaya: Erlangga.Surbakti, Theresa Adelina Victoria. 2012. Effect of Corporate Characteristics and Tax Reform on Tax Avoidance on Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2008-2010 Period. University of Indonesia.